Understanding spectator sustainable transportation intentions in international sport tourism events - Martins, Rute (2021)
It is vital to study spectator responses to environmental campaigns to advance environmental sustainability initiatives. Therefore, this investigation aimed to identify which factors influence spectator sustainable transport intentions and perform a spectator segmentation based on their responses. Data were collected from 355 spectators at an international surfing event hosted in a renowned surfing destination. The data were analysed in two stages. First, through the sport sustainability campaign evaluation model to infer spectator sustainable transport intentions. Second, through non-hierarchical cluster analysis, to segment the sample based on those intentions. The results added a direct relationship between the points of attachment and sustainable transport intentions. Furthermore, the results highlighted the effect of constraints, points of attachment and past sustainable behaviours as predictors of spectator sustainable transport intentions. In addition, differences in needs (i.e., aesthetic), attachment to the community, lack of time, lack of access and past sustainable behaviours were found within the three analysed clusters. Organisers of sport tourism events should develop sustainable transport campaigns promoting the destination’s aesthetic features, strengthening the connection between the local community and the event spectators, and improving the availability of information on transport services to increase spectator commitment to more sustainable modes of transport.